Glycyrrhizin Attenuates Salmonella Typhimurium-Induced Tissue Injury, Inflammatory Response, and Intestinal Dysbiosis in C57BL/6 Mice - Wang, Baikui; Ye, Xiaolin; Zhou, Yuanhao; Zhao, Pengwei; Mao, Yulong (Frontiers in Veterinary Science, 2021)
Salmonellae are one of the most important foodborne pathogens, which threaten the health of humans and animals severely. Glycyrrhizin (GL) has been proved to exhibit anti-inflammatory and tissue protective properties. Here we investigated the effects of GL on tissue injury, inflammatory response and intestinal dysbiosis in S. Typhimurium-infected mice. Results showed that GL or gentamicin (GM) significantly (P < 0.05) alleviated ST-induced splenomegaly indicted by the decreased spleen index, injury of liver and jejunum indicated by the decreased hepatocytic apoptosis and the increased jejunal villous height. GL significantly (P < 0.05) increased secretion of inflammatory cytokines (IFN-γ, IL-12p70, IL-6, IL-10) in spleen and IL-12p40 mRNA expression in liver. Meanwhile, GL or GM pre-infection treatments significantly (P < 0.05) decreased ST-induced pro-inflammatory cytokines (IFN-γ, TNF-α, IL-6) expression both in spleen and liver and increased (P < 0.05) anti-inflammatory cytokine IL-10 secretion in spleen. Furthermore, GL or GM pre-infection treatment also regulates the diversities and compositions of intestinal microbiota and decreased the negative connection among the intestinal microbes in ST-infected mice. The above findings indicate that glycyrrhizin alleviates ST-induced splenomegaly, hepatocytic apoptosis, injury of jejunum and liver, inflammatory response of liver and spleen, and intestinal dysbacteriosis in mice.